Will Kentucky Route Zero Take You to Twin Peaks? Tracing the Narrative of the American Weird - Serada, Alesha (Filmiverkko, 2021)
In this article, I analyze the narrative of Kentucky Route Zero in search of tropes and constructive principles already known from Twin Peaks. I seek to find out how interactivity of the game adds to these tropes and techniques, and whether we can project our findings about its interactive hypertextual narrative back to Twin Peaks. I suggest that, in both cases, the fictional world largely emerges from the interaction with the audience that actively interprets the narrative and extends it far beyond the ‘tangible’ text. Furthermore, the authors explicitly call for such involvement by introducing self-reflexivity and metacommentary in their work. I conclude with the perspective of the American Weird setting, implemented in both ‘story worlds’; it can engender new meanings that surpass the linear logic of narration.
Keywords: cybertext; fan studies; hypertext; intertextuality; metatext; narrative; video games; fi=Viestintätieteet|en=Communication Studies|